Ozempic: Revolutionary weight loss drug or too good to be true? - Iram Shakil (BioScientist: The Salford Biomedicine Society Magazine, 2024)
The drug Ozempic, also known as semaglutide, has gained popularity in recent years due to its rapid weight loss effects. It was first created as a treatment for patients with type 2 diabetes suffering with obesity. Numerous studies including meta-analyses have found that semaglutide is effective in achieving weight loss but also has adverse gastrointestinal effects such as nausea, diarrhoea and vomiting. It has been seen to influence the brain, as semaglutide crosses the blood-brain barrier to reduce satiety centres that in turn reduce appetite, which further supports weight loss. Although semaglutide has adverse effects, some studies have shown that it may help patients who have cardiovascular disease reduce cardiovascular events such as myocardial infarction. Ozempic has been proven to be effective as a weight loss treatment despite its side effects and more studies are being done to see how long-term use may affect patients.